Burden of care and quality of life in caregivers of patients presenting in manic episode of bipolar affective disorder (Journal of Psychiatrists' Association of Nepal, 2025)
Background: Bipolar affective disorder is a chronic mood disorder characterized by manic, depressive, hypomanic, or mixed episodes, often leading to considerable caregiver burden. This study assesses the burden of care and quality of life (QOL) in caregivers of patients experiencing manic episodes.Methodology: A cross-sectional descriptive study was conducted at the Mental Hospital, Lagankhel, involving 65 caregivers recruited through convenience sampling. Data were collected using a semi-structured proforma, WHO-QOL-BREF for QOL assessment, and BAS for burden evaluation. Sociodemographic and clinical associations with QOL and burden were analyzed using appropriate statistical tools.Results: Significant differences in QOL scores were associated with caregiver age, sex, relationship with the patient, and education level. Multiple linear regression showed that patient’s education, number of episodes, family history, caregiver’s age, and occupation significantly influenced QOL. Higher burden scores were found among caregivers with lower education and socioeconomic status. A negative correlation was observed between burden and QOL scores.Conclusion: Caregivers who were older, female, parents, or had lower education reported poorer QOL. Patient-related factors and caregiver demographics influenced QOL. Higher caregiver burden was linked to lower QOL, emphasizing the need for supportive interventions targeting at-risk caregiver populations.